A critical look at an Islamic Gold investment account - Asadov, Alam I.; Abdul Halim, Asyraf; Rozlan, Ahmad R. M.; Rahamat, Amri; Mustaffa Kamil, Nazrol Kamil (2016)
This article assesses an Islamic gold investment account offered by an Islamic bank in Malaysia and analyses its pros and cons. We look into the product’s relative advantages and disadvantages compare to some other Islamic deposit products and conventional gold accounts. In process of the assessment we also come across some Shari’ah compliance related issues and some practices which needs to be scrutinized from Shari’ah, economic and social perspectives. Overall, our findings suggest the account to be worthwhile investment instrument for long-term saving instrument and promising venture at times of boom in gold prices. However, the account is considered as a risky and unfavorable investment when gold price is on fall or if the customer intends to keep his deposits for a brief period. Finally, we pose some questions to the reader to ponder upon about some possible implication of the product for the Islamic bank, its customer or the society at large.